Predictive influence of spirituality, peers and parents attachment on youth delinquency: a perspective of Nigerian students in Malaysia - Idowu, Grace Tanimoonwo; Hassan, Siti Aishah (Australian Academy of Business and Social Sciences, 2014)
This paper proposes a theoretical model that integrates the different groups of factors which influence the behaviour of Nigerian students in Malaysia. The design / methodology that was adopted involves presentation of hypothetical model which shows youth delinquency behaviors among Nigerian students in Malaysia universities as a dependent variable been influenced by a set of three independent variables such as: spirituality, peers and parents attachment. These variables, whether consciously or unconsciously influenced the behaviour of Nigerian students in Malaysia. The limitations of this study stem from the nature of the study itself. Being a preliminary study, it aims to integrate the factors identified in the existing literature that influenced youth delinquency among international students in Malaysia with emphasis on the Nigerian students; thus, future research on the subject will examine the existing relationships among the aforementioned factors. In particular, it will analyze the weight of each factor and the relative importance of each element. Therefore, determining the relative importance of each element and factor would constitute an important source of information for future work on international student’s behavioural formation and development studies. Since, there are few studies which try to tackle the influence of spirituality, peers and parent’s attachment on behavioural formation of Nigerian students in Malaysian universities from an integrated point of view, this paper contributes to bridging that gap.